Modulation of Acid Sphingomyelinase in Melanoma Reprogrammes the Tumour Immune Microenvironment - Emma Assi; Davide Cervia; Laura Bizzozero; Annalisa Capobianco; Sarah Pambianco; Federica Morisi; Clara De Palma; Claudia Moscheni; Paolo Pellegrino; Emilio Clementi; Cristiana Perrotta (Mediators of Inflammation)
The inflammatory microenvironment induces tumours to acquire an aggressive and immunosuppressive behaviour. Since acid sphingomyelinase (A-SMase) downregulation in melanoma was shown to determine a malignant phenotype, we aimed here to elucidate the role of A-SMase in the regulation of tumour immunogenic microenvironment using in vivo melanoma models in which A-SMase was either downregulated or maintained at constitutively high levels. We found high levels of inflammatory factors in low A-SMase expressing tumours, which also displayed an immunosuppressive/protumoural microenvironment: high levels of myeloid-derived suppressor cells (MDSCs) and regulatory T lymphocytes (Tregs), as well as low levels of dendritic cells (DCs). In contrast, the restoration of A-SMase in melanoma cells not only reduced tumour growth and immunosuppression, but also induced a high recruitment at tumour site of effector immune cells with an antitumoural function. Indeed, we observed a poor homing of MDSCs and Tregs and the increased recruitment of CD8+ and CD4+ T lymphocytes as well as the infiltration of DCs and CD8+/CD44high T lymphocytes. This study demonstrates that change of A-SMase expression in cancer cells is sufficient per se to tune in vivo melanoma growth and that A-SMase levels modulate immune cells at tumour site. This may be taken into consideration in the setting of therapeutic strategies.